2001
DOI: 10.1038/sj.bmt.1702846
|View full text |Cite
|
Sign up to set email alerts
|

Megatherapy combining I131 metaiodobenzylguanidine and high-dose chemotherapy with haematopoietic progenitor cell rescue for neuroblastoma

Abstract: Summary:Despite the use of aggressive chemotherapy, stage 4 high risk neuroblastoma still has very poor prognosis which is estimated at 25%. Metabolic radiotherapy with I 131 MIBG appears a feasible option to enhance the effects of chemotherapy. Seventeen patients having MIBGpositive residual disease received 4.1-11.1 mCi/kg of I 131 MIBG 7-10 days before initiating the high-dose chemotherapy cycle consisting of busulphan 16 mg/kg and melphalan 140 mg/m 2 followed by PBSC infusion. We compared the toxicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 14 publications
2
35
0
2
Order By: Relevance
“…Despite recent advances in treatment, neuroblastoma remains a relatively lethal tumor, accounting for 10% of pediatric cancers but 15% of cancer deaths in children. 15 In the last few years, metabolic radiotherapy including 131 I-meta-iodobenzylguanidine scintigraphy has been used in the treatment of advanced neuroblastomas in order to enhance the effects of chemotherapy with peripheral blood progenitor cell transplantation (PBSCT), 16 though it has not been accepted as the preferred therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in treatment, neuroblastoma remains a relatively lethal tumor, accounting for 10% of pediatric cancers but 15% of cancer deaths in children. 15 In the last few years, metabolic radiotherapy including 131 I-meta-iodobenzylguanidine scintigraphy has been used in the treatment of advanced neuroblastomas in order to enhance the effects of chemotherapy with peripheral blood progenitor cell transplantation (PBSCT), 16 though it has not been accepted as the preferred therapy.…”
Section: Discussionmentioning
confidence: 99%
“…38 Preliminary results of the association of melphalan with TBI and MIBG demonstrate the feasibility of such a regimen. [39][40][41] High doses of MIBG alone or in combination with topotecan 42 or other radiosensitizing agents such as CDDP 43,44 followed by PBSCR have been piloted with early promising results in poor responding or relapse patients. 9.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Incorporation of high-dose 131 I-MIBG treatment into HDCT/auto-SCT might be an option although it also results in late effects. [10][11][12][13][14][15] Matthay et al 15 showed that incorporation of high-dose 131 I-MIBG treatment into HDCT/auto-SCT was feasible and effective in patients with refractory neuroblastoma. However, no studies to date have incorporated high-dose 131 I-MIBG treatment into tandem HDCT/ auto-SCT for treating newly diagnosed high-risk patients.…”
Section: Discussionmentioning
confidence: 99%